2017
DOI: 10.1007/s10393-017-1211-7
|View full text |Cite
|
Sign up to set email alerts
|

Summarizing US Wildlife Trade with an Eye Toward Assessing the Risk of Infectious Disease Introduction

Abstract: The aim of this study was to characterize the role of the USA in the global exchange of wildlife and describe high volume trade with an eye toward prioritizing health risk assessment questions for further analysis. Here we summarize nearly 14 years (2000–2013) of the most comprehensive data available (USFWS LEMIS system), involving 11 billion individual specimens and an additional 977 million kilograms of wildlife. The majority of shipments contained mammals (27%), while the majority of specimens imported were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 12 publications
0
112
0
1
Order By: Relevance
“…There are many complex multifaceted socio-economic, biological and ecological factors that influence a country's risk of transmitting zoonotic diseases of wild animal origin and its ability to respond to them (Devitt, 2017). The volumes of live wild animals traded between countries is only one of those important factors; yet a proper understanding of this particular trade dynamic is important and can help to direct limited resources (such as funds and expertise) currently available to prevent zoonotic disease outbreaks (Karesh et al, 2005;Pavlin et al, 2009;Smith et al, 2009). In this regard, our review of the CITES Trade Database identified a number of countries that warrant particular attention: China (the largest exporter of live mammals with 98,979 animals representing 58.7% of all such trade), Nicaragua (the largest exporter of live amphibians with 122,592 animals representing 53.8% of all such trade), South Africa (the largest exporter of live birds with 889,607 animals representing 39.2% of all such trade) and Peru (the largest exporter of live reptiles with 1,675,490 animals representing 18.8% of all such trade).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many complex multifaceted socio-economic, biological and ecological factors that influence a country's risk of transmitting zoonotic diseases of wild animal origin and its ability to respond to them (Devitt, 2017). The volumes of live wild animals traded between countries is only one of those important factors; yet a proper understanding of this particular trade dynamic is important and can help to direct limited resources (such as funds and expertise) currently available to prevent zoonotic disease outbreaks (Karesh et al, 2005;Pavlin et al, 2009;Smith et al, 2009). In this regard, our review of the CITES Trade Database identified a number of countries that warrant particular attention: China (the largest exporter of live mammals with 98,979 animals representing 58.7% of all such trade), Nicaragua (the largest exporter of live amphibians with 122,592 animals representing 53.8% of all such trade), South Africa (the largest exporter of live birds with 889,607 animals representing 39.2% of all such trade) and Peru (the largest exporter of live reptiles with 1,675,490 animals representing 18.8% of all such trade).…”
Section: Discussionmentioning
confidence: 99%
“…The USA was the biggest importer of live mammals legally (63,672 animals representing 62.4% of all such mammal trade between 2012 and 2016) and live amphibians (135,327 animals; 63.6% of such trade between 2012 and 2016). In fact, the USA is the global leader in illegal and legal wildlife consumption and between 2000 and 2009, more than 1.48 billion live animals were legally imported to USA where 92% of imports were for commercial purposes, largely the pet trade (Smith et al, 2009(Smith et al, , 2017. Although the USA was second to Hong Kong with regards to legal live reptile imports, it still involved 1,275,892 individual animals and represented 14.3% of all such live trade between 2012 and 2016.…”
Section: Rankmentioning
confidence: 99%
See 1 more Smart Citation
“…This holds great potential for the development of new tools to predict parasite host breadths (H P and H O in our proposed framework), a key component of understanding disease transmission dynamics at the landscape level [56,77]. Additionally, ecophylogenetics may provide insights on potential spillover events that could result in disease emergence, a highly relevant topic under global change and increased international movement of species leading to shifts in host communities and translocation of parasites to new areas and hosts [79,80]. Adoption of the host-space framework under ecophylogenetics could improve epidemiological surveillance, allowing early targeting of potentially suitable hosts (HP) [62,63].…”
Section: From Disease Distributions To Risk Mappingmentioning
confidence: 99%
“…7 Based upon these summary findings and stakeholder prioritization, three separate Risk Assessments were performed: Aquatic, amphibian, and invertebrate species accounted for approximately 50% of these live shipments, mainly imported by the aquatic and pet industries.…”
Section: Risk Assessmentmentioning
confidence: 99%